Metakaolin-based geopolymers: Efflorescence and its effect on microstructure and mechanical properties. Issue 2 (15th January 2022) - Longhi, Márlon A.; Rodríguez, Erich D.; Walkley, Brant; Eckhard, Diego; Zhang, Zuhua; Provis, John L.; Kirchheim, Ana P.
Abstract: Efflorescence in geopolymers results from mobility of excess alkali and consequent crystallization of alkali carbonates. Efflorescence potential of various geopolymers has been reported previously but the knowledge regarding the effect of efflorescence on the microstructure and mechanical properties of geopolymers remains limited. In this work, metakaolin-based geopolymers were exposed to air, partially immersed in water, and fully immersed, to simulate different processes involved in efflorescence formation. The mechanical properties were assessed by compressive, splitting tensile and flexural strengths, and linear deformation. The microstructural features were investigated by SEM, synchrotron XRD, multinuclear MAS NMR, MIP and synchrotron X-ray microtomography. Extensive efflorescence resulted in a reduction of mechanical strength and changes in the nanostructure and microstructure, which is different from observations for Portland cement-based materials, where efflorescence is usually regarded as a surface or aesthetic problem. The understanding of the relationship between efflorescence formation, the synthesis and exposure conditions provides important insight into the manufacturing and application conditions of geopolymer related materials.